Challenges of Local Government in Formation of New Autonomous Regions - Radjak, Darwin Abd.; Ibrahim Tjan, Abdul Halil Hi.; Suhu, Bakri La (Universitas Tribhuwana Tunggadewi, 2025)
The formation of new regions does not merely mean reducing the administrative area so that government functions can be carried out more optimally, it also reduces the level of their political alienation so that people rediscover their role in the dynamics of government politics in their region. The concurrent creation of autonomous areas is the emergence of an independent status based on the goals and actual circumstances of the local population in a specific region or area as a component of the Indonesian nation and national territory. The objective of this study is to undertake a research and understanding process based on a technique that examines human problems and societal phenomena using a qualitative approach. Using a spiral data analysis paradigm, information was gathered via observations, interviews, and documentation.. The results of the study are that the formation of new autonomous regions is a process carried out so that autonomous regions can have a strong autonomous status as provincial capitals, so that the process of forming this autonomous region is very important and must be considered, but the approach of community proposals or community participation is important, this stage must go through from below (grass roots). Third, it cannot be denied that economic factors are one of the main triggers for the desire to form autonomous regions, because every new region is entitled to an allocation of funds. Pembentukan daerah otonom baru tidak hanya berarti pengurangan wilayah administratif agar fungsi pemerintahan dapat dijalankan secara lebih optimal, tetapi juga mengurangi tingkat keterasingan politiknya sehingga masyarakat dapat menemukan kembali perannya dalam dinamika politik pemerintahan di daerahnya. Pembentukan daerah otonom secara bersamaan adalah munculnya status kemandirian berdasarkan tujuan dan keadaan nyata penduduk setempat di suatu daerah atau wilayah tertentu sebagai komponen bangsa dan wilayah nasional Indonesia. Tujuan penelitian ini adalah untuk melakukan proses penelitian dan pemahaman berdasarkan teknik yang mengkaji permasalahan manusia dan fenomena kemasyarakatan dengan menggunakan pendekatan kualitatif. Dengan menggunakan paradigma analisis data spiral, informasi dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pembentukan daerah otonom baru merupakan proses yang dilakukan agar daerah otonom dapat memiliki status otonomi yang kuat sebagai ibu kota provinsi, sehingga proses pembentukan daerah otonom ini sangat penting dan harus diperhatikan, namun pendekatan usulan masyarakat atau partisipasi masyarakat menjadi penting, tahapan ini harus melalui dari bawah (akar rumput). Ketiga, tidak dapat dipungkiri bahwa faktor ekonomi menjadi salah satu pemicu utama keinginan untuk membentuk daerah otonom, karena setiap daerah baru berhak mendapatkan alokasi dana.